Where Carbon Goes When Water Flows: Carbon Cycling across the Aquatic Continuum - Ward, Nicholas D.; Bianchi, Thomas S.; Medeiros, Patricia M.; Seidel, Michael; Richey, Jeffrey E.; Keil, Richard G.; Sawakuchi, Henrique O. (Frontiers in Marine Science, 2017)
The purpose of this review is to highlight progress in unraveling carbon cycling dynamics across the continuum of landscapes, inland waters, coastal oceans, and the atmosphere. Earth systems are intimately interconnected, yet most biogeochemical studies focus on specific components in isolation. The movement of water drives the carbon cycle, and, as such, inland waters provide a critical intersection between terrestrial and marine biospheres. Inland, estuarine, and coastal waters are well studied in regions near centers of human population in the Northern hemisphere. However, many of the world’s large river systems and their marine receiving waters remain poorly characterized, particularly in the tropics, which contribute to a disproportionately large fraction of the transformation of terrestrial organic matter to carbon dioxide, and the Arctic, where positive feedback mechanisms are likely to amplify global climate change. There are large gaps in current coverage of environmental observations along the aquatic continuum. For example, tidally-influenced reaches of major rivers and near-shore coastal regions around river plumes are often left out of carbon budgets due to a combination of methodological constraints and poor data coverage. We suggest that closing these gaps could potentially alter global estimates of CO2 outgassing from surface waters to the atmosphere by several-fold. Finally, in order to identify and constrain/embrace uncertainties in global carbon budget estimations it is important that we further adopt statistical and modeling approaches that have become well-established in the fields of oceanography and paleoclimatology, for example.